Hyperglycemia aggravates ischemic brain damage via ERK1/2 activated cell autophagy and mitochondrial fission - Liu, Ping; Yang, Xiao; Niu, Jianguo; Hei, Changchun (Frontiers in Endocrinology, 2022)
Background: Hyperglycemia is one of the major risk factors for stroke and stroke recurrence, leading to aggravated neuronal damage after cerebral ischemia/reperfusion (I/R). ERK1/2 signaling pathway plays a vital role in cerebral ischemic injury. However, the role of the ERK1/2 pathway in hyperglycemia-aggravated ischemic brain damage is not clear. Methods: Streptozotocin (STZ; 50 mg/kg)-induced diabetes (blood glucose ≥12 mmol/L) or control groups in adult Sprague-Dawley rats were further subdivided into I/R (carotid artery/vein clamping), I/R + PD98059 (I/R plus ERK1/2 inhibitor), and Sham-operated groups (n = 10 each). Neurobehavioral status (Neurological behavior scores) and the volume of the cerebral infarction (TTC staining); brain mitochondrial potential (JCI ratio test) and cell apoptosis (TUNEL assay); RAS protein expression, phosphorylated/total ERK1/2 and Drp-1 (Dynamic-related protein 1) protein levels (Western blotting); mitochondrial fusion-related proteins mitofusin-1/2 (Mfn1/2), optic atrophy (OPA-1) and mitochondrial fission 1 (Fis1), and autophagy-associated proteins Beclin-1, LC3-I/II and P62 (Western blotting and immunohistochemistry) were analyzed. Results: The I/R + PD98059 group demonstrated better neurobehavior on the 1st (p < 0.05) and the 3rd day (p < 0.01) than the I/R group. Compared to the Sham group, cerebral ischemia/reperfusion brought about neuronal damage in the I/R group (p <0.01). However, treatment with PD98059 showed an improved situation with faster recovery of mitochondrial potential and less apoptosis of neuronal cells in the I/R + PD98059 group (p < 0.01). The I/R group had a higher-level expression of RAS and phosphorylated ERK1/2 and Drp-1 than the diabetes mellitus (DM) group (p < 0.01). The PD98059 treated group showed decreased expression of p-ERK1/2, p-Drp-1, Fis1, and Beclin-1, LC3-I/II and P62, but increased Mfn1/2 and OPA-1 than the I/R group (p < 0.01). Conclusion: Hyperglycemia worsens cerebral ischemia/reperfusion-induced neuronal damage via ERK1/2 activated cell autophagy and Drp-1-dependent mitochondrial fission. Keywords: Hyperglycemia; Cerebral ischemic injury; ERK1/2; Drp-1; Mitochondrial fission; Cell autophagy.